Pengaruh Perubahan Kebijakan Fiskal Terhadap Perilaku Konsumen: Tinjauan dari Perspektif Ekonomi Makro - Udin Bahrudin1; Edy Suranta Karina Sembiring (Hikamatzu | Journal of Multidisciplinary, 2024)
This research aims to analyze the influence of changes in fiscal policy on consumer behavior from a macroeconomic perspective. The type of research is literature review, data collection with documentation, data analysis with CLR. Fiscal policies implemented by the government have a significant impact on consumer behavior in society. Changes in fiscal policy, such as changes in tax rates or public spending, can affect levels of household consumption, investment, and savings, as well as cause shifts in the allocation of economic resources. Factors such as disposable income, inflation expectations, and monetary policy also play an important role in determining consumer reactions to fiscal policy. Therefore, an in-depth understanding of the transmission mechanisms of fiscal policy and consumer responses to them is crucial for policy makers in planning effective and sustainable economic strategies